TOPONYMS, BRAND NAMES FORMED ON THE BASIS OF PLACE NAMES - Sabo Akhmadalieva Murodovna; Shavkatova Navruza Zoirjonovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
This research synthesizes the numerous literature streams concerning toponymy and brand naming through an exploration of place branding practices. Before looking at the concerns of endogenous and exogenous contestation that surround place name commodification, the study expands on the concept of place name commodification beyond the scant attention it has received within existing toponymy research. The paper's conclusion explores how the commodification of locations as brand names, with their corresponding brand values and visuals, has the ability to limit users' alternative place perceptions and, in turn, the natural possibility for cocreating the place 'product' and its associated value.